Desain Kemasan Karung Yang Optimal Untuk Pengemas Bahan Curah - Lusi Zafriana (Jurnal Teknik Industri, 2010)
Many bulk material like cement, salt, and other primer  consumer goods product using of plastic bag package made from polipropilen. Because size of the packaging hardly depend on tidy material types, hence it’s required an optimization design of size plastic bag that matching with material type ( bulk density) and tidy product weight. Applied simple mathematics algorithm, where volume value karung will be converted to bulk material weight, hence optimization oflengthe and wide karung matching with bulk density material filled in in packaging will be able to be determined. Using trial error method, value l ( wide) and p ( length) plastic bag,hence expected plastic bag will be able to load material as heavy m kilogram. For example, if we want to design plastic bag for packaging dry rice 20 kgs with bulk density 0,8 kg/litre, hence we obtained optimal size of karung with wide 43 cm and long 75 cm.